Hyperstructures and some of the most recent applications - Piergiulio Corsini (Journal of Hyperstructures)
After a brief history of Hypergroups, since the beginning around the 40s till today, one gives an excursus of the most recent applications of this topic to Fuzzy Sets and Chinese groups as HX-hypergroups.